Fracture toughness enhancement of brittle nanostructured materials by spatial heterogeneity: A micromechanical proof for CrN/Cr and TiN/SiOx multilayers. (15th August 2016) - Daniel, Rostislav; Meindlhumer, Michael; Zalesak, Jakub; Sartory, Bernhard; Zeilinger, Angelika; Mitterer, Christian; Keckes, Jozef
Abstract: The search for simultaneously strong and tough materials requires the development of novel design strategies and synthesis routes. In this work, it is demonstrated that a nanoscale variation in material mechanical property distributions can serve as a universal concept for improvement of fracture behavior of nanostructured brittle thin films. Mechanical tests performed on microcantilever beam specimens of multilayered TiN/SiOx thin films show that the fracture toughness of this hierarchical, microstructurally and mechanically heterogeneous material can be enhanced up to 60% with respect to either of its single-layered constituents, which is attributed to a large difference in their elastic modulus. Similarly, micro-bending tests of multilayered CrN/Cr thin films reveal an increase in fracture toughness of 40% with respect to CrN and Cr single layers. In this case, the enhancement of fracture toughness is attributed to the difference in strength of both constituents. These results indicate that the fracture toughness enhancement in brittle nanostructured films is conditioned by simultaneously occurring microstructural heterogeneity and a difference in the intrinsic mechanical properties of the material constituents, which ensure an effective increase of energy dissipation through the alternation of the crack path and crack deflection at the interfaces. Graphical abstract: Highlights: A universal concept for fracture toughness enhancement of brittle nanostructured films is proposed. The concept relies on microstructural heterogeneity and a difference in the intrinsic mechanical properties. An increase of energy dissipation by the crack deflection at the interfaces ensures enhancement of the fracture toughness.